MENINGKATKAN KERJA SAMA SISWA PADA PEMBELAJARAN PRAKTIK AKUNTANSI DAGANG MELALUI TEAM BASED LEARNING KELAS XI AKUNTANSI SMK NEGERI 2 JAKARTA - Diah Safitri, Niken; Dwi Kismayanti Respati; Umi Widyastuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student Collaboration is one of the essential 21stcentury skills included in the 4C competencies (Creativity, Critical Thinking, Communication, and Collaboration). This skill is important to be developed in the learning process because it can enhance students’ communication and collaboration abilities. However, preliminary observations indicated that students' collaboration was still not optimal, as shown by low participation in group discussions and limited communication among students. This study aimed to improve students' collaboration through the implementation of the Team-Based Learning (TBL) model. This study employed Classroom Action Research (CAR), which was conducted in two cycles using a descriptive qualitative approach. The research subjects consisted of 34 class XI Accounting students at SMK Negeri 2 Jakarta. The sampling technique used was non-probability sampling with purposive sampling based on predetermined criteria. The results showed that the implementation of Team-Based Learning was able to improve students' collaboration in each cycle. The average collaboration score increased from 75 in the pre-cycle to 84 in Cycle I and 93 in Cycle II. The improvement was indicated by increased students' active participation in group discussions, communication skills, individual responsibility in completing group tasks, and mutual respect among group members. Therefore, the Team-Based Learning model was proved effective in improving students' collaboration in Accounting Practice learning.